2010
DOI: 10.1182/blood-2009-08-233155
|View full text |Cite
|
Sign up to set email alerts
|

Results of a phase 2 study of bortezomib in patients with relapsed or refractory indolent lymphoma

Abstract: This study evaluated the efficacy and safety of single-agent bortezomib in indolent B-cell lymphoma that had relapsed from or was refractory to rituximab. Sixty patients enrolled: 59 were treated with bortezomib 1.3 mg/m 2 on days 1, 4, 8, and 11 for up to eight 21-day cycles; responders could receive 4 additional cycles; maintenance was optional. Fifty-three evaluable patients completed more than 2 cycles. The median age was 70 years, 53% female, Ann Arbor stage III-IIIE (28%) and IV (65%); 43 patients (72%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 14 publications
2
62
0
Order By: Relevance
“…The results of this trial led to the Food and Drug Administration approval of Btz for treatment of relapsed MCL. Di Bella et al 61 reported results of Btz in patients with indolent lymphoma who had relapsed after rituximab therapy. Six of 36 FL and 1 of 6 patients with marginal zone lymphoma had objective responses; however, many were noted to have stable disease.…”
Section: Nfb Modulation With the Use Of Proteasome Inhibitorsmentioning
confidence: 99%
“…The results of this trial led to the Food and Drug Administration approval of Btz for treatment of relapsed MCL. Di Bella et al 61 reported results of Btz in patients with indolent lymphoma who had relapsed after rituximab therapy. Six of 36 FL and 1 of 6 patients with marginal zone lymphoma had objective responses; however, many were noted to have stable disease.…”
Section: Nfb Modulation With the Use Of Proteasome Inhibitorsmentioning
confidence: 99%
“…5,8 The clinical activity in MCL is remarkable, with reported response rates that are twice as high as in other B-cell non-Hodgkin lymphoma subtypes. 9 Bortezomib is also highly active as a single agent in multiple myeloma (MM), 10 Waldenstrom macroglobulinemia, 11 and systemic light-chain amyloidosis, 12 inducing responses in 38%, 44%, and 57% of relapsed patients, respectively. In contrast, single-agent bortezomib has no significant clinical activity in several types of leukemia, in Hodgkin lymphoma, and in most solid tumors, despite often promising preclinical activity.…”
Section: Introductionmentioning
confidence: 99%
“…To date, bortezomib, which reversibly inhibits the 26S proteasome, is the only proteasome inhibitor for which phase ii data in relapsed and refractory fl are available (Table iii). Three phase ii studies have examined bortezomib as monotherapy in relapsed and refractory fl, demonstrating variable orrs ranging from 17% to 77%, with few complete remissions [37][38][39] . Median pfs and os were available in one study and were reported to be 5.1 and 27.7 months respectively 38 .…”
Section: Proteasome Inhibitorsmentioning
confidence: 99%
“…Three phase ii studies have examined bortezomib as monotherapy in relapsed and refractory fl, demonstrating variable orrs ranging from 17% to 77%, with few complete remissions [37][38][39] . Median pfs and os were available in one study and were reported to be 5.1 and 27.7 months respectively 38 . The most frequent grades 3 and 4 toxicities included thrombocytopenia, neutropenia, fatigue, neuropathy, and diarrhea.…”
Section: Proteasome Inhibitorsmentioning
confidence: 99%